2016
DOI: 10.1080/01431161.2016.1252474
|View full text |Cite
|
Sign up to set email alerts
|

Airborne radiation mapping: overview and application of current and future aerial systems

Abstract: Nuclear power and associated activities are never far from scrutiny, the apparent advantages of the technology are juxtaposed by the risk of incidents perceived as being catastrophic. If a major nuclear incident was to occur, an important aspect of the response management to any radionuclide release would be the need to rapidly establish the spatial distributions and quantities of these released radionuclides, their type in addition to their corresponding activity. The data received from surveys would directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 49 publications
0
71
0
Order By: Relevance
“…// Low Variance Resampling [24] function algorithm type: gradient computation related studies non-robust fully decentralized [3], [10], [11] robust (k = 2) decentralized current paper max. information gain centralized [1], [2], [4]- [6] is N = N 1 × N 2 = 5000 × 100. We consider Gaussian distribution to for both the perception and the detection model.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…// Low Variance Resampling [24] function algorithm type: gradient computation related studies non-robust fully decentralized [3], [10], [11] robust (k = 2) decentralized current paper max. information gain centralized [1], [2], [4]- [6] is N = N 1 × N 2 = 5000 × 100. We consider Gaussian distribution to for both the perception and the detection model.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Focusing on nuclear environment, wall climbing robots have been popular for inspecting undamaged steam generators at nuclear sites [7]. The authors in [8] provide an overview of aerial robots for radiation mapping, while [9] develops a drone equipped with sensors for nuclear risk characterization. Inspection of outdoor environments is primarily done with the aid of GPS.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a UAV platform for aerial survey has facilitated the advance of aerial survey methodology. A good review of recent publications can be found here [13].…”
Section: Introductionmentioning
confidence: 99%